Pengembangan Pesantren Muhammadiyah Siaga COVID-19 dengan Ketahanan Pangan melalui Pendekatan Konsep Helix - Emma Rachmawati; Esty Martiana Rachmie; Hidayati Hidayati; Yuyun Umniyatun; Deni Wahyudi Kurniawan; Lia Karisma Saraswati; Virgo Sulianto Gohardi; Eka Wulandari; Mochamad Iqbal Nurmansyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The Covid-19 pandemic has impacted various sectors such as health, social, economy, including education. Pondok Pesantren (Islamic Boarding School) is one of the educational institutions affected by the emergence of the Covid-19 pandemic. For this reason, efforts are needed in the form of Covid-19 alert activities and increasing the food security of Islamic boarding schools in the face of the COVID-19 pandemic. This activity was carried out during 2020, located at Pondok Pesantren in Bogor Regency and Depok City. This activity adopts the concept of multi-stakeholder involvement or the Helix model, namely educational institutions, business, government, and society. This community service activity consists of several activities, including Design and Distribution of Health Promotion Media related to COVID-19, Creating and duplicating Food Security Strategy (Lele Kangkung/Lekung), Online Workshop and Orientation of COVID-19, Making handwashing places in Islamic Boarding School, Monitoring and Evaluation of health behavior in Islamic Boarding School environment.